Absence of streaming plasma waves around noontime over Thumba in recent times: Is it related to the movement of the dip equator? - Sekar, R.; Gupta, S.P.; Acharya, Y.B.; Chakrabarty, D.; Pallamraju, D.; Pathan, B.M.; Tiwari, D.; Choudhary, R.K. (My University, 2013)
Systematic ground-based magnetometer measurements from Thumba (8.47°N, 76.6°E) and Tirunelveli (8.73°N, 77.8°E), India, revealed a movement of the magnetic dip equator towards the south. The magnetic dip angle measured over Thumba increased by about 2° during 1985–2010. In view of the movement of the dip equator over Thumba, the dependence of the generation of streaming plasma waves on the dip angle is examined. An order of magnitude calculation using the results obtained from the thin-shell model of the electrojet is performed. The calculation suggests that the streaming waves over Thumba during magnetically quiet periods at noontime exist when the dip angle is <1.5° and that these waves are generally absent whenever the dip angle is ≥1.5°. Evidence based on in situ rocket and ground-based radar measurements is provided by comparing earlier and recent observations.
Keywords: Streaming plasma waves; Movement of the magnetic dip equator; E-region irregularities; Dip equator; Tirunelveli; Thumba